1999
DOI: 10.1104/pp.121.4.1273
|View full text |Cite
|
Sign up to set email alerts
|

An Expansin Gene Expressed in Ripening Strawberry Fruit

Abstract: Tissue softening accompanies the ripening of many fruit and initiates the processes of irreversible deterioration. Expansins are plant cell wall proteins proposed to disrupt hydrogen bonds within the cell wall polymer matrix. Expression of specific expansin genes has been observed in tomato (Lycopersicon esculentum) meristems, expanding tissues, and ripening fruit. It has been proposed that a tomato ripening-regulated expansin might contribute to cell wall polymer disassembly and fruit softening by increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
0
3

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(95 citation statements)
references
References 32 publications
3
89
0
3
Order By: Relevance
“…For example, ripening-regulated and cell wall-related cDNAs such as expansin (F22), extensin-like/Prorich protein (F93), and polygalacturonase (D15) did not show any change in expression as a result of the auxin treatment (Table IV), whereas pectate lyase (E30) and endo-1,4-␤-glucanase (E80) were repressed (Table III). Our observation that not all ripeningregulated cell wall-related genes in strawberry are auxin dependent is supported by a previous study on the strawberry expansin gene FaExp2, which was reported to be auxin insensitive (Civello et al, 1999). Interestingly, FaExp2 expression was also not affected by ethylene treatment.…”
Section: Auxin and Gene Expression In Strawberry Development And Ripesupporting
confidence: 77%
See 1 more Smart Citation
“…For example, ripening-regulated and cell wall-related cDNAs such as expansin (F22), extensin-like/Prorich protein (F93), and polygalacturonase (D15) did not show any change in expression as a result of the auxin treatment (Table IV), whereas pectate lyase (E30) and endo-1,4-␤-glucanase (E80) were repressed (Table III). Our observation that not all ripeningregulated cell wall-related genes in strawberry are auxin dependent is supported by a previous study on the strawberry expansin gene FaExp2, which was reported to be auxin insensitive (Civello et al, 1999). Interestingly, FaExp2 expression was also not affected by ethylene treatment.…”
Section: Auxin and Gene Expression In Strawberry Development And Ripesupporting
confidence: 77%
“…Apart from extensins, which are specifically associated with secondary walls of TEs (Fukuda, 1997), the expression of expansin genes was recently correlated with primary cell wall expansion and secondary cell wall thickening during Z. elegans TE development in vitro (Im et al, 2000). It is possible that the pectate lyase and expansin enzymes previously identified in strawberry as ripening regulated and associated with cell wall metabolism in the receptacle cells (Medina-Escobar et al, 1997;Civello et al, 1999) might be involved in remodeling the cell wall during the development of the vascular system.…”
Section: Analogy In Gene Expression Between Strawberry Fruit Developmmentioning
confidence: 99%
“…Nevertheless, expansin transcripts are most abundant in actively growing organs, such as leaf primordia in tomato (Fleming et al, 1997(Fleming et al, , 1999Reinhardt et al, 1998), internodes in rice (Cho and Kende, 1997b), pollen in maize (Zea mays; Cosgrove et al, 1997) and soybean (Crowell, 1994), pistil in tobacco (Pezzotti et al, 2002), fruits in strawberry (Fragaria spp. ; Civello et al, 1999) and tomato (Brummell et al, 1999a(Brummell et al, , 1999b, and coleoptiles in oat , indicating that they are involved in critical developmental processes. To date, however, most experiments with expansin genes have not clarified the roles of each Table I…”
Section: Temporal and Spatial Expression Of The Gmexp1 Gene During Romentioning
confidence: 99%
“…The slight reduction of the decrement in firmness that occurs during the transition from the green to the white stage in apel fruits suggests that other cell wall-degrading mechanisms are taking place in unripe fruit. EGase (Harpster et al, 1998;Llop-Tous et al, 1999;Trainotti et al, 1999) and expansin (Civello et al, 1999) genes are candidates for cell wall degradation at these stages. Suppression of PME activity does not affect firmness during normal ripening, and suppression of beta-subunit protein accumulation increases softening (Brummel and Harpster, 2001).…”
Section: Pectate Lyasementioning
confidence: 99%